1997
DOI: 10.1111/j.1365-2133.1997.tb01562.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo expression of IL-4, IL-5, IL-13 and IFN-γ mRNAs in peripheral blood mononuclear cells and effect of cyclosporin A in a patient with Kimura's disease

Abstract: Semiquantitative reverse transcription-polymerase chain reaction was used to analyse the expression of cytokine mRNAs in freshly isolated peripheral blood mononuclear cells obtained from a patient with Kimura's disease. The patient was treated with cyclosporin A (CsA) after incomplete tumour resection and irradiation of lesions. Levels of interleukin (IL)-4, IL-5 and IL-13 mRNA were elevated and the level of interferon (IFN)-gamma mRNA was within normal limits before treatment. The levels of IL-4, IL-5 and IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 24 publications
1
58
0
Order By: Relevance
“…However, there is a possibility that mast cells secrete these cytokines in the lesions of Kimura’s disease by this slow degranulation mechanism. It has been reported that Kimura’s disease was completely cured and IL-4 and IL-5 expression decreased to a minimum level by surgical resection or radiotherapy [20]. These findings suggest the possibility that the skin lesion itself provides some factors that increase IL-4 and IL-5 levels in Kimura’s disease patients.…”
Section: Discussionsupporting
confidence: 47%
“…However, there is a possibility that mast cells secrete these cytokines in the lesions of Kimura’s disease by this slow degranulation mechanism. It has been reported that Kimura’s disease was completely cured and IL-4 and IL-5 expression decreased to a minimum level by surgical resection or radiotherapy [20]. These findings suggest the possibility that the skin lesion itself provides some factors that increase IL-4 and IL-5 levels in Kimura’s disease patients.…”
Section: Discussionsupporting
confidence: 47%
“…The mainstay of therapy has been oral corticosteroids, even though steroid withdrawal can result in recurrence. Recently, 3 cases of successful treatment of Kimura’s disease with cyclosporine have been described [10, 11, 12]. In our case, the treatment with cyclosporine rapidly improved the subcutaneous nodules accompanied by the improvement of peripheral blood eosinophilia.…”
Section: Discussionmentioning
confidence: 56%
“…Several studies reported that the serum levels of Th2-type cytokines such as IL-4, IL-5, and IL-13 were elevated [10, 11, 12]. In another study, activated lymphocytes released cytokines such as GM-CSF and TNF-α, and these released cytokines caused eosinophil activation [24].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies reported that lymphocytes and mast cells were important in the pathogenesis of ALHE [10, 11, 12, 22, 23]although ALHE is known as an eosinophilic inflammatory disorder. Several studies reported that the serum levels of Th2-type cytokines such as IL-4, IL-5, and IL-13 were elevated [10, 11, 12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation